2020
DOI: 10.1177/0272684x20974547
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Substance Abuse Amongst Adolescents and Young Adults in Ikenne Local Government, Ogun State, Nigeria

Abstract: Substance abuse describes the unsafe use of psychoactive substances. It leads to dependence on the abused substance with subsequent development of health disorders and mortality. Globally, millions of adolescents and young adults from low and middle income countries are prone to substance abuse with consequent far reaching impact on national development. This study was done to assess the perception of substance abuse amongst the adolescents and young adults in Ikenne local government area, Ogun State, Nigeria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Another possible reason is peer pressure which the youth today find a way to enforce on their friends to join them in illicit acts such as abuse of drugs. This was confirmed through some past findings of the studies conducted by Lawal & Aliyu (2020), Alabi, et al (2020), Sarkingobir et al (2020), Alimi, et al (2020) and Olowo (2020) in which participants confirmed being involved in abuse of drugs as a result of peer pressure. Also, this finding may be linked to the fact that the abusers among the student-teachers have been into the act before they gained admission into the college.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Another possible reason is peer pressure which the youth today find a way to enforce on their friends to join them in illicit acts such as abuse of drugs. This was confirmed through some past findings of the studies conducted by Lawal & Aliyu (2020), Alabi, et al (2020), Sarkingobir et al (2020), Alimi, et al (2020) and Olowo (2020) in which participants confirmed being involved in abuse of drugs as a result of peer pressure. Also, this finding may be linked to the fact that the abusers among the student-teachers have been into the act before they gained admission into the college.…”
Section: Discussionsupporting
confidence: 71%
“…Lawal and Aliyu (2020) assessed the causes of drugs and substances abuse among youth in Katsina Metropolis. Similarly, Alabi et al (2020) investigated the perception of substance abuse amongst adolescents and young adults in Ikenne Local Government, Ogun State. Yahaya (2019) investigated the effect of drug abuse among youth in Nasarawa Local Government, Kano State.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations